Behavior management in dentistry for children - Wright, Gerald Z.; Kupietzky, Ari; Wright, Gerald Z. (John Wiley & Sons Inc., 2014)
Guiding patient behavior is as important as ever for the practicing dentist, and the behavior of pediatric patients is perhaps the most challenging to manage. Drs. Wright and Kupietzky here update Dr. Wright's classic work on managing pediatric dental patients. Behavior Management in Dentistry for Children,2nd Edition, has been entirely rewritten and includes the latest and most effective management strategies from an international team of experts in the field. The book addresses the influence of family and parenting styles on children's behavior and the.